Recent advances in the synthesis and application of fluorescent α-amino acids. Issue 38 (5th September 2016) - Harkiss, Alexander H.; Sutherland, Andrew
Abstract : The design and synthesis of new fluorescent α-amino acids as well as their application in imaging of biological systems has been reviewed. Abstract : Fluorescence spectroscopy has become a powerful technique for probing a range of complex biological processes including enzyme mechanisms and protein–protein interactions. While the application of this technique uses a number of strategies, many of these rely on the use of fluorescent α-amino acids. This review highlights the recent synthetic methods developed for the incorporation of highly conjugated chromophores into the side-chain of α-amino acids and the application of these compounds as probes for imaging in medicine and biology. In particular, the design and synthesis of α-amino acids bearing coumarin, flavone and polyaromatic derived chromophores is described.